2021
DOI: 10.1101/2021.05.27.445967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The 3-phosphoinositide-dependent protein kinase 1 is an essential upstream activator of protein kinase A in malaria parasites

Abstract: Cyclic AMP (cAMP) signalling is crucial for the propagation of asexual malaria blood stage parasites. Recent work on Plasmodium falciparum demonstrated that phosphorylation of the invasion ligand AMA1 by the catalytic subunit of cAMP-dependent protein kinase A (PfPKAc) is an essential step during parasite invasion into red blood cells. However, the exact mechanisms regulating PfPKAc activity are only partially understood and PfPKAc function has not been extensively studied in gametocytes, the sexual blood stag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 93 publications
(164 reference statements)
1
7
0
Order By: Relevance
“…This is in line with previous work showing that a hierarchical PfPKA-and PfGSK3βmediated phosphorylation of the cytoplasmic domain of AMA1 is a prerequisite for efficient red blood cell invasion (7)(8)(9)(10)16) and that the use of kinase-specific inhibitors blocks this essential process (8,10,36). In contrast to PfPKA, that was shown to be absolutely essential for red blood cell invasion using conditional knockout systems (9,16,19), PfGSK3β does not appear to be as essential for this process (Figures 2A+3C). This partial redundancy of this kinase might be based on i) that GSK3-specific phosphorylation only enhances the efficiency of red blood cell invasion or ii) that another kinase such as PfCK2 can functionally complement PfGSK3β activity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in line with previous work showing that a hierarchical PfPKA-and PfGSK3βmediated phosphorylation of the cytoplasmic domain of AMA1 is a prerequisite for efficient red blood cell invasion (7)(8)(9)(10)16) and that the use of kinase-specific inhibitors blocks this essential process (8,10,36). In contrast to PfPKA, that was shown to be absolutely essential for red blood cell invasion using conditional knockout systems (9,16,19), PfGSK3β does not appear to be as essential for this process (Figures 2A+3C). This partial redundancy of this kinase might be based on i) that GSK3-specific phosphorylation only enhances the efficiency of red blood cell invasion or ii) that another kinase such as PfCK2 can functionally complement PfGSK3β activity.…”
Section: Discussionsupporting
confidence: 92%
“…The P. falciparum genome encodes for 65 eukaryotic protein kinases ( 22 ), of which various members have already been described to be involved in essential processes, including egress, host cell invasion, or gametocytogenesis ( 17 , 19 , 38 , 53 ). Nevertheless, to date, only one malaria targeting kinase inhibitor has reached the phase of clinical trials: the PI4K-inhibitor MMV390048 was shown to be safe and well tolerated with high antimalarial activity against all stages of the parasitic life cycle except hypnozoites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular function of all these kinases remains unclear. However, TGGT1_239420 was previously linked to the development of artemisinin resistance in vitro 82 and the Plasmodium falciparum ortholog of TGGT1_268210 was recently linked to regulation of protein kinase A (PKA) 83 .…”
Section: Analysis Of Delayed-death Genes Reveals Two Kinases That Regulate Invasionmentioning
confidence: 99%